Potentially inappropriate medications among elderly Brazilian outpatients - Faustino, Christine Grützmann; Passarelli, Maria Cristina Guerra; Jacob-Filho, Wilson (São Paulo Medical Journal, 2013)
CONTEXT AND OBJECTIVES: In Brazil, few studies have investigated the prevalence of potentially inappropriate medications (PIMs) among elderly outpatients. This study aimed to determine the prevalence of PIMs prescribed for elderly outpatients, identify the PIMs most commonly involved, and investigate whether age, sex and number of medications are related to prescription of such medications. DESIGN AND SETTING: Observational descriptive study developed in the Geriatrics Service of the Central Institute of Hospital das Clínicas (HC), Faculdade de Medicina da Universidade de São Paulo (FMUSP), São Paulo, Brazil. METHODS: Prescriptions issued to 1,270 elderly patients (≥ 60 years) were gathered from a database. These prescriptions had been written by geriatricians at a tertiary-level university hospital in São Paulo, Brazil, between February and May 2008. The prescriptions were divided according to sex and age group (60-69, 70-79 and ≥ 80). The Beers criteria were used to evaluate PIMs. RESULTS: Most of the sample comprised women (77%) and the mean age was 80.1 years. The mean prevalence of PIM prescriptions was 26.9%. Female sex and number of medications prescribed were associated with prescription of PIMs. The chance of having a PIM prescription was lower among patients ≥ 70 years. CONCLUSION: The greater prevalence of PIMs was correlated with female sex. The chance of having a PIM prescription was lower among patients ≥ 70 years and became greater with increasing numbers of medications prescribed (≥ 7).